Parents’ and Teachers’ Cooperation: Mutual Expectations and Attributions from a Parents’ Point of View - Kruger, Jana; Michalek, Ruth (International Journal about Parents in Education, 2023)
According to Oevermann, there is a working bond between both teacher and individual student and between teacher and the entire class. Parents are depicted as a ‘third party’ involved in the process of constituting and shaping this working bond. An account of such a teacher-student bond with its innate antinomy and paradox can for instance be found in the work of Helsper. Our article aims at examining more closely the bond between teacher and parents from a parents’ point of view. For this purpose, guided interviews have been conducted with 27 parents. Following grounded theory methodology, we develop a theory about parents’ views on mutual expectations, in particular with regard to the respective competence of teachers and parents. This underlines how the parent-teacher relationship is characterized by contradictions and expectations that form upon those attributions. The analyses offer a basis for a possible professionalization focus in teacher education.